Distribution of hydrocarbons in the estuarine area of the Northern Dvina River during seasonal flood. - Nemirovskaya, Inna A (PANGAEA, 2011)
Heavy contaminant load released into the Northern Dvina River during flooding increased the concentrations of aliphatic (AHC) and polcyclic aromatic (PAH) hydrocarbons in water and bottom sediments. The composition of hydrocarbons was different from that of the summer low flow season. The concentrations of dissolved and particulate AHC ranged from 12 to 106 and from 192 to 599 µg/l, respectively, and bottom sediments contained from 26.2 to 329 µg/g AHC and 4 to 1785 ng/g PAH. As the transformation of AHC occurred at low spring temperatures, the alkane composition was shown to be dominated by terrigenous compounds, whereas more stable PAH showed elevated contents of petrogenic and pyrogenic compounds. It was also shown that the Northern Dvina-Dvina Bay geochemical barrier prevents contaminant input into the White Sea, i.e., acts as a marginal filter.
Organic geochemistry of water and bottom sediments during a seasonal flood in 2006 in the North Dvina River estuary
Keywords: Archive of Ocean Data; ARCOD